Novel method of preparation of blue crude copper phthalocyanine having the grennish shade - Nurul Farhana, Alias (2012)
Copper Phthalocyanine (CuPc) is a blue pigment; CuPc is the most stable pigment towards light, temperature and chemical. Hence, combined with its attractive colors, this pigment is widely used in many applications such as in water-based and solvent-based paints and inks including automotive paints, textiles and plastics with the temperature of operation up to 350°C. In this work the greenish shade of Blue Crude CuPc which is required in the industries is obtained by adding a portion of Sodium Hydroxide (NaOH) in the preparation of Blue Crude CuPc. Crude also have been synthesized by using copper (1) ascorbic because the emission of ascorbic acid to the crude preparation produce a very green shade of the CuPc crude as well as the a-pigment CuPc. Characterization by using Fourier Transform Infrared spectroscopy (FTIR) was done to prove the presence of hydroxyl group. Then apigment was conducted to prove that synthesis greenish blue crude is better than doing colour mixing of pigment. Eventhough 3-pigment should be done to show better greenish blue pigment but since it is not accessible to the kneader, it was replaced with cc-pigmentation. Meanwhile the colour presence was tested by using chromameter. This instrument will automatically show the colour and shade of the sample without taking long time. However, black and white calibration should be done before used.